Rotas para recuperação de ferro fino contido no underflow do espessador de lama da Usina de Conceição - Paulo Sergio de Oliveira (2006)
This work investigated the possibility to produce concentrate of iron ore that attends to the chemical specifications of pellet feed for the production of direct reduction pellets, using as feed the slime thickener underflow from Conceição´s beneficiation plant, by applying unit operations of desliming, magnetic separation and flotation. The increased demand of iron ore motivates the development of technologies for optimizing existing processes or of new processes for use of ores of low grade. The underflow mass flow rate of the slime thickener in Conceição´s plant isapproximately 180t/h. The underflow in spite of containing contaminants at significant levels, mainly (Al2O3, SiO2, and P), they represent mineral particles fully liberated at fractions below 75 micrometers. The process team from Itabira research center performed the mineralogical characterization of the material aiming at the possible recovery of iron from the underflow stream current sent to tailings pond. At the preliminary part of this work, samples of the slime thickener underflow had theirglobal mineralogy and grain size distribution levels analyzed and they were also chemically analyzed with the objective of determining their composition and also what were their main contaminants (SiO2, Al2O3 and P). When it comes to the mineralogical aspect it was confirmed that at the fraction +0,045mm the main SiO2 bearer is quartz, and this last represents 20% of the mass. At the -0,045mm, the hematite corresponds to close to 55% and the caolinite, which is an aluminum silicate occurs as a more abundant gange mineral. xv At the fraction (-0,045mm + 0,020mm), the quartz is responsible for almost all the SiO2presence, and at the fraction (-0,009mm) the caolinite is responsible for 70,0% of the total presence of SiO2. The Aluminum main sources are Caolinite, Muscovite, and Gibbsite. The fraction (-0,009mm), which represents 36,8% of the global sample, has to be rejected to the tailings pond, because it has very high levels of P=0,167%, Al2O3=18,0%.Recovery and concentrate quality obtained in the present work can be considered as satisfactory regarding the objectives o this research. When considering the recirculation of cleaner tails in a continuous industrial operation further increase in recovery is expected.The best option of studied concentration consisted of the circuit use of desliming in hydrocyclones and concentration for flotation. The concentrate obtained presented a high iron grade (mainly in the form of granular hematite) and a low P grade.